2022
DOI: 10.36469/30184
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Assessment of Weight Change in African American Females and Hispanics with HIV-1 After Initiating Integrase Strand-Transfer Inhibitors or Protease Inhibitors

Abstract: Background: Studies have shown an increase in weight among people living with HIV (PLWH) who initiated integrase strand transfer inhibitors (INSTI). However, weight gain with INSTI-based regimens vs other regimens in females or racial/ethnic minorities is poorly understood. Objective: This study assessed differences in weight gain among treatment-naïve, female, African Americans and Hispanics after initiating INSTI-based vs protease inhibitor (PI)-based regimens. Methods: This retrospective, observational co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…Thus, while these studies demonstrated a relationship between weight gain and INSTI use, potential confounders including age, initial BMI, CD4 count, HIV viral load, gender and ethnicity can influence this relationship [ 12 , 13 , 16 , 21 24 ]. For instance, several studies investigating the effects of ART in PWH have observed a heightened risk of weight gain after the initiation of ART in women PWH [ 15 , 23 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while these studies demonstrated a relationship between weight gain and INSTI use, potential confounders including age, initial BMI, CD4 count, HIV viral load, gender and ethnicity can influence this relationship [ 12 , 13 , 16 , 21 24 ]. For instance, several studies investigating the effects of ART in PWH have observed a heightened risk of weight gain after the initiation of ART in women PWH [ 15 , 23 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data are reassuring, considering that among INIs, DTG is the most involved in weight gain [ 46 ]. However, we would underline that our cohort of patients involved predominantly white males, whereas integrase inhibitor-related weight gain was more frequently observed in females and those from a black African background among PLWH [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the aforementioned studies have looked specifically at T2DM risk, many studies have assessed purely ART-associated weight change. As an example, a recent study showed that ART was associated with weight and BMI gain after initiating treatment, along with a significantly greater mean weight gain (1.5 kg) in Black female PLWH who initiated an INSTI compared to a PI over a mean follow-up of 9.5 months [ 30 ]. Findings in Hispanic PLWH also trended in the same direction [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, a recent study showed that ART was associated with weight and BMI gain after initiating treatment, along with a significantly greater mean weight gain (1.5 kg) in Black female PLWH who initiated an INSTI compared to a PI over a mean follow-up of 9.5 months [ 30 ]. Findings in Hispanic PLWH also trended in the same direction [ 30 ]. The importance of the results of this current study is that they bridge the gap between research like the one just mentioned above, which is investigating ART and weight gain, by isolating the impact of ART-associated weight gain on cardiometabolic outcomes.…”
Section: Discussionmentioning
confidence: 99%